A poly(urethane)-encapsulated benzo[2, 3-d:6, 7-d′]diimidazole organic down-converter for green hybrid LEDs. (13th February 2020) - Wiles, Alan A.; Bruckbauer, Jochen; Mohammed, Nabeel; Cariello, Michele; Cameron, Joseph; Findlay, Neil J.; Taylor-Shaw, Elaine; Wallis, David J.; Martin, Robert W.; Skabara, Peter J.; Cooke, Graeme
Abstract : A novel green emissive material embedded in a resin provides efficient down-conversion in a hybrid LED. Abstract : The development of organic down-converting materials continues to attract attention in hybrid LED technology by obviating the need for non-sustainable rare-earth elements. In this work, a benzodiimidazole-based system (TPA-BDI ) has been employed as a down-converting layer in a hybrid organic–inorganic LED device. A commercially available poly(urethane)-based resin is used as the encapsulating material, providing a dilute layer of TPA-BDI that is deposited on top of the GaN-based LED. Crucially, the solution-state emissive performance is generally maintained when encapsulated at low concentrations within this resin. A maximum luminous efficacy of 87 lm W −1 was demonstrated using a 1.0 mg ml −1 concentration of TPA-BDI in the resin. The suitability of using organic down-converters to produce green light from hybrid devices was demonstrated by the excellent repeatability of the device characteristics across a series of encapsulated LEDs.